The effect of agrochemical and agrotechnical methods of recultivation of oil-polluted soil on productivity of spring rape - A. R. Ravzutdinov; M. Yu. Gilyazov; S. Zh. Kuzhamberdieva (Зерновое хозяйство России)
Oil is considered to be the most widely spread pollutant of soil. We have studied the possibility of natural rehabilitation of oil-polluted grey forestry soil and efficiency of some agrochemical and agrotechnical methods of its recultivation in the Predkamie of the Republic of Tatarstan. The methods of recultivation, which have been applied, are mechanical tillage (loosening), liming, fertilizing with minerals and biomedicine ‘Baykal EM-1’. The article summarizes the data about the effect of the tested methods of recultivation of oil-polluted soil on productivity of spring rape, which was grown according to the scheme of crop rotation after 3,7 and 11 years of soil contamination with oil. The negative influence on productivity of spring rape after the only oil pollution during 11 years has been established. At the same time there has been seen a close positive correlation between the limitation of soil contamination and productivity (R2=0.804÷0.996), that shows the possibility of a gradual, albeit slow detoxication of grey forestry soil without any recultivation. The significance of the tested methods of recultivation has changed a lot along the time. At the beginning (after three years of pollution) intensive loosening had a more positive effect on productivity of spring rape, then the effect of it decreased at a large increase of the effect of total mineral fertilizing. Liming of oil-polluted low-acid grey forestry soil produced no effect on productivity increase. The maximum productivity of spring rape has been obtained in the experiment ‘loosening+liming+NPK’.